PCS antenna design the challenge of miniaturization. - Skrivervik, A.K (IEEE Antennas & propagation magazine.)
PCS (personal communication system) devices have become an important part of everyday life. The pressure to design small, lightweight, and user-friendly mobile-communication devices has increased accordingly, creating the need for optimal antennas for mobile applications. In this paper, we present some basic rules about electrically small antennas, give clues and guidelines about efficient antenna miniaturization, and, finally, show some examples of miniature antennas developed in our laboratory for practical applications.